Validasi Metode Analisis Penetapan Kadar 4-Amino-3-Nitrophenol Dalam Pewarna Rambut Oksidator - Prabaning Budi, Hasti Kusuma; Zahara, Zahara (Badan Pengawas Obat dan Makanan, 2023)
4-amino-3-nitrophenol (C6H6N2O3) has been widely used as an oxidative hair colourant. This compound was a structural isomer of 2-amino-4-nitrophenol (2,4-ANP) and 2-amino-5-nitrophenol (2,5-ANP). All of these compounds have different regulations in Indonesia. The maximum concentration of 4-amino-3-nitrophenol in oxidative hair colourants was 1.5% after being mixed with oxidator agents. Otherwise, 2-amino-4-nitrophenol and 2-amino-5-nitrophenol were prohibited substances contained in cosmetic products. Therefore, it was essential to validate the method to differentiate all these three compounds with a resolution of more than 1.5. The High-Performance Liquid Chromatography with Photo Diode Array Detector using octadecylsilane (C18) column (250 mm x 4.6 mm and 5 μm particle size) has been developed and validated. Acetonitrile HPLC grade and 0.05 M acetic buffer with pH 5.9 (20:80) have been used as mobile phase isocratically. The flow rate and column temperature were 1.0 ml/minute and 40oC, respectively. The validation result showed good linearity, with the correlation coefficient of the method being 1.0. The method is also selective in differentiating all three compounds and is specific to the methylparaben compound. The precision data on the concentration of 3.68 μg/ml, 14.70 μg/ml and 18.38 μg/ml was 0.59%, 1.92% and 0.68% respectively. The percent recovery of this method on the same concentration above was 100.17-100.91, 99.06-100.39 and 100.38-101.05, respectively. The limit quantitation of this method was 0,07%. All validation parameters of the method have met the requirement so that the analysis method for determination of 4,3-ANP has been proven to be selective, accurate and reliable.